2016
DOI: 10.1039/c5cp07422c
|View full text |Cite
|
Sign up to set email alerts
|

Understanding adsorption of CO2, N2, CH4 and their mixtures in functionalized carbon nanopipe arrays

Abstract: The selective adsorption behaviours of carbon dioxide, methane and nitrogen on bundles of functionalized CMK-5 are investigated at 303 K using grand-canonical Monte Carlo simulations. Functional groups (-OH, -COOH) cause a significant enhancement in CO2 uptake (up to 19.5% at a pressure of 38.13 bar for -COOH). On the other hand, the adsorption amount of methane decreases with respect to bare CMK-5 by ∼13% (at 38.13 bar) upon functionalization. Furthermore, functionalized CMK-5 with different pore sizes (4 nm,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 63 publications
0
16
0
Order By: Relevance
“…For example, Bhatia et al , have modeled silicon-carbide derived nanoporous carbon and studied its significance in gas transport for CO 2 and CH 4 . In another study, Halder et al have modeled an experimentally observed porous structure of CMK-5 and studied its applicability in gas separation. They have reported that functionalized CMK-5 models show better gas separation ability compared to various activated carbons.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, Bhatia et al , have modeled silicon-carbide derived nanoporous carbon and studied its significance in gas transport for CO 2 and CH 4 . In another study, Halder et al have modeled an experimentally observed porous structure of CMK-5 and studied its applicability in gas separation. They have reported that functionalized CMK-5 models show better gas separation ability compared to various activated carbons.…”
Section: Introductionmentioning
confidence: 99%
“…The code has been used in earlier works to study the adsorption phenomenon in porous materials. 20,28 Theory of Adsorption. In GCMC simulations, we get the absolute number of adsorbed particles (N ad ) in the simulation box.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, although CO 2 is a linear molecule without a dipole moment, it has high quadrupolar moment and polarizability values, which means the adsorbent CO 2 interaction can be enhanced by strengthening the surface electric field, for example, oxidation of carbons by concentrated HNO 3 ‐induced oxygen‐bearing surface groups, and this polarized surface showed enhanced CO 2 adsorption . The enhancement of CO 2 adsorption by ‐OH and ‐COOH groups was also proved by grand‐canonical Monte Carlo simulations …”
Section: Carbon‐based Co2 Adsorbentsmentioning
confidence: 80%
“…101,102 The enhancement of CO 2 adsorption by -OH and -COOH groups was also proved by grand-canonical Monte Carlo simulations. 103 The manipulation of surface chemistry has a profound influence on the adsorption strength towards CO 2 , but this does not necessarily result in the increasing of adsorption capacities because the texture properties of porous materials normally decrease with the introduction of external functionalities.…”
Section: Influence Of Surface Chemistry On Co 2 Adsorption For Carbonsmentioning
confidence: 99%